2000
DOI: 10.1046/j.1365-3083.2000.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐SSA/Ro Antibody Determination by Enzyme‐Linked Immunosorbent Assay as a Supplement to Standard Immunofluorescence in Antinuclear Antibody Screening

Abstract: The aim of this study was to investigate the frequency and possible clinical relevance of SSA/Ro antibodies, as determined by enzyme-linked immunosorbent assay (ELISA), in patient sera not exhibiting a concomitant positive reaction by the standard immunofluorescence (IF) test using HEP-2 cells as substrate. SSA/Ro reactivity, as shown by ELISA, was found in 285 (7%) of 4025 serum samples consecutively remitted for antinuclear antibody (ANA) screening. Seventy-five of these serum samples (26%), derived from 64 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
2
11
1
2
Order By: Relevance
“…Routine laboratory diagnosis in SS and SLE includes the use of immunofluorescence or ID to evaluate the presence of autoAb's against SSA and SSB antigens (3). Several reports have suggested that these classical techniques are less sensitive than Western blot and ELISA for the detection of anti-SSA-52 antibodies (38)(39)(40). Our data confirm these findings and show that among 13 SS and 12 SLE patients who were reported to have no detectable anti-SSA antibodies by ID, six (four SS and two SLE) were found by ELISA to possess measurable antibodies against SSA-52.…”
supporting
confidence: 88%
“…Routine laboratory diagnosis in SS and SLE includes the use of immunofluorescence or ID to evaluate the presence of autoAb's against SSA and SSB antigens (3). Several reports have suggested that these classical techniques are less sensitive than Western blot and ELISA for the detection of anti-SSA-52 antibodies (38)(39)(40). Our data confirm these findings and show that among 13 SS and 12 SLE patients who were reported to have no detectable anti-SSA antibodies by ID, six (four SS and two SLE) were found by ELISA to possess measurable antibodies against SSA-52.…”
supporting
confidence: 88%
“…In many studies, IFA has been used to define cohorts of CTD patients, potentially excluding patients with a CTD who are ANA negative by IFA (21,22). Our data suggest that there may be some antibodies that react with antigens not well represented or "hidden" in the HEp-2 cells, such as SS-A, or that may bind to specific epitopes with increased exposure in the solid-phase EIA (23)(24)(25)(26). To further complicate the comparison, approximately 5% of samples negative by both IFA (≤1:40) and EIA (≤1.0 U) were found to be positive on the MIA method.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the ANA test is not sufficiently specific to establish a diagnosis of a CTD, and a more specific confirmatory test, such as an anti-doublestranded DNA (dsDNA) or an anti-ENA antibody test, is indicated. With the exception of antibodies to cytoplasmic antigens such as Jo-1 (histidyl-tRNA synthetase), it is rare to have a positive anti-ENA antibody test in the absence of a positive ANA test when acetone-fixed HEp-2 cells are used as the substrate for IIF (3,14,31). Thus, the finding of ANA-negative SLE due to the use of SS-A antigen-poor substrates such as mouse liver is no longer a valid consideration.…”
Section: Indications For Ena Testingmentioning
confidence: 99%